Evaluation of the relationship between hemoglobin levels and thrombolysis in myocardial infarction risk score in patients with non-st elevation acute coronary syndrome - Geçmen, Çetin; Güler, Ekrem; Babur, Gamze Güler; Elveran, Ali; Güneş, Hacı Murat; Aguş, Hicaz Zencirkıran; Karaca, İbrahim Oğuz; Keleş, Nurşen; Esen, Özlem; Esen, Ali Metin (My University, 2016)
Introduction: The relationship between hemoglobin (Hb) levels at admission and the thrombolysis in myocardial infarction (TIMI) risk score in patients with non-ST elevation acute coronary syndrome (NSTEACS) was investigated. Patients and Methods: In total, 286 NSTE-ACS patients were included in the study. Hb levels and biochemical parameters were measured at admission. The patients were grouped into the following three groups according to the TIMI risk score: low-intermediate-, and high-risk groups. Results: Hb levels (in g/dL) at admission in low-, intermediate-, and high-risk groups were 13.5 ± 1.9, 12.5 ± 1.9, and 11.3 ± 1.9, respectively (p < 0.001). We found a negative moderate correlation between Hb levels and TIMI risk scores (r= -0.408, p < 0.001). In univariate regression analysis, it was found that with the increase in the TIMI risk score, Hb levels at admission were signifi cantly reduced (estimate= -0.406; p< 0.001; 95% confi dence interval; -0.521 to -0.290). Conclusion: We found that as the TIMI risk score of patients admitted to hospital presenting with NSTEACS increased, their Hb levels at admission correspondingly decreased. Thus, the simple and commonly measured Hb level can be a useful parameter in stratifying the risks of patients presenting with NSTE-ACS during admission.

Giriş: ST yükselmesiz akut koroner sendrom hastalarının geliş hemoglobin seviyesi ile TIMI risk skoru arasındaki ilişki araştırıldı.Hastalar ve Yöntem: ST yükselmesiz akut koroner sendromlu 286 hasta çalışmaya dahil edildi. Tüm hastaların geliş anında hemoglobin ve biyokimyasal parametreleri çalışıldı. Hastalar TIMI risk skoruna göre düşük, orta ve yüksek risk olarak 3 gruba ayrıldı.Bulgular: Geliş hemoglobin seviyesi (g/dL) düşük, orta ve yüksek TIMI risk grubunda sırasıyla (13.5 ± 1.9, 12.5 ± 1.9, 11.3 ± 1.9, p< 0.001) olarak saptandı. Hemoglobin seviyesi ve TIMI risk skoru arasında orta düzeyde negatif korelasyon bulundu (r: -0.408, p< 0.001). Tek değişkenli regresyon analizinde TIMI risk skoru artışı ile geliş hemoglobin seviyelerinin önemli derecede düşük olduğu saptandı (Estimate; -0.406, p< 0.001, %95 GA[-0.521-(-0.290)].Sonuç: ST yükselmesiz akut koroner sendrom ile hastaneye yatırılan hastaların risk skoru attıkça geliş hemoglobin seviyelerinin bağlantılı olarak düşük olduğu tespit edildi. Basit ve yaygın bir test olarak kullanılan hemoglobin seviyesi, ST yükselmesiz akut koroner sendrom hastalarının geliş anındaki risk durumunu belirlemede kullanılabilir.
ST yükselmesiz akut koroner sendrom hastalarında TIMI risk skoru ile hemoglobin değeri arasındaki ilişkinin değerlendirilmesi
Keywords: Myocardial Infarction; Hemoglobins; Acute Coronary Syndrome; Miyokart İnfarktüsü; Hemoglobinler; Akut Koroner Sendrom